The resurrection of an immature upper anterior tooth: a case report - Sivan, Hema Devi; Azih, Nurul Farah; Mustaffa, Musliana (IIUM Press, 2024)
Revascularization of necrotic dental pulp has regained interest as an alternative treatment for immature permanent teeth. An 18-year-old female patient was referred for management of an immature upper anterior tooth with symptomatic apical periodontitis. Patient presented with an unsightly tooth 21 with no symptoms. Patient experienced dental trauma approximately 10 years ago. Clinical examination revealed a light-yellow discoloration with Class IV composite restoration on tooth 21, no carious lesion, Grade 1 tooth mobility, tenderness to percussion, and probing depths within normal limit. Periapical radiograph of tooth 21 revealed a periapical lesion, root of normal length but thin root dentin, and an open apex. Revascularization of tooth 21 was carried out in two visits. The first visit focused on disinfection of the root canal, while the second visit focused on the induction of bleeding followed by placement of mineral trioxide aggregate (MTA). The 6-month and 24-month follow-up visits revealed an absence of periapical lesion, although a significant reduction in the size of root apex could not be observed. An immature permanent tooth presents clinical challenges that affects both the short-term and the long-term treatment outcomes, therefore, an appropriate case selection taking into consideration various factors, and the skills and experience of the clinician are of upmost importance to ensure the predictability of the treatment provided. This procedure could eliminate intraradicular infection, however, increased dentin thickness on the root canal wall could not be observed, suggesting an indeed challenging procedure despite meticulous technical steps to perform the procedure.